Bairro Concórdia em Belo Horizonte: entrave ou oportunidade à cidade-negócio? - Junia Maria Ferrari de Lima (2009)
In the current scenery of the Brazilian cities it is easy to observe an increasingly unbalanced occupation of the urban land, with a prevalence of the peripheral concentration by a low-income population, contrasting with an uneven concentration of urban equipment and services in the central areas. At the same time, there is a growing submission of the urban land to the action of the real estate capital, in search of the maximum profit in providing dwellings in our cities, favored in several aspects by the action of the State: Be it through public investments, the prevalent social-economic model or the legislation. However, some sections of the urban land are obstacles to the real estate marketexpansion, although they present many of the conditions that are necessary to its action. In spite of the privileged location and access, together with an allowing legislation regarding the utilization coefficient and occupation rate, some urban areas remain relatively unchanged and not greatly transformed in relation to the adjoining areas. This paper sheds light on the elements that made possible this interdiction tothe real estate market, through the study of Bairro Concordia in Belo Horizonte, the occupation characteristics of which remained the same along its 80 years of history, despite its privileged location in relation to the central city infrastructure. The juridical institute of emphyteusis becomes a central element in the discussion about the subject, through the analysis of its use as a way of distribution of the neighborhood lots and as one of the probable causes of the local population fixation. So the purpose here is to contribute to the discussions in the range of the current urban planning, which searches for testified effectivitytools for the implementation of the concept of Social Function of the Property and the City.